104k views
1 vote
Simplify: 6(a + 1) -4 (8a - 5)

Show all steps please!

User OrpqK
by
5.0k points

1 Answer

1 vote

Answer:


\large\boxed{6(a+1)-4(8a-5)=-26a+26}

Explanation:


6(a+1)-4(8a-5)\qquad\text{use distributive property}\ a(b+c)=ab+ac\\\\=(6)(a)+(6)(1)+(-4)(8a)+(-4)(-5)\\\\=6a+6-32a+20\qquad\text{combine like terms}\\\\=(6a-32a)+(6+20)\\\\=-26a+26

User Santosh Ghimire
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.